Genetic Defects in Phosphoinositide 3-Kinase δ Influence CD8+ T Cell Survival, Differentiation, and Function - Cannons, Jennifer L.; Preite, Silvia; Kapnick, Senta M.; Uzel, Gulbu; Schwartzberg, Pamela L. (Frontiers in Immunology, 2018)
Activated phosphoinositide 3-kinase delta syndrome (APDS), also known as p110 delta activating mutation causing senescent T cells, lymphadenopathy and immunodeficiency (PASLI), is an autosomal dominant primary human immunodeficiency (PID) caused by heterozygous gain-of-function mutations in PIK3CD, which encodes the p110 catalytic subunit of PI3K. This recently described PID is characterized by diverse and heterogeneous clinical manifestations that include recurrent respiratory infections, lymphoproliferation, progressive lymphopenia, and defective antibody responses. A major clinical manifestation observed in the NIH cohort of patients with PIK3CD mutations is chronic Epstein-Barr virus (EBV) and/or Cytomegalovirus viremia. Despite uncontrolled EBV infection, many APDS/PASLI patients had normal or higher frequencies of EBV-specific CD8+ T cells. In this review, we discuss data pertaining to CD8+ T cell function in APDS/PASLI, including increased cell death, expression of exhaustion markers, and altered killing of autologous EBV-infected B cells, and how these and other data on PI3K provide insight into potential cellular defects that prevent clearance of chronic infections.